2021
DOI: 10.1186/s40634-021-00339-w
|View full text |Cite
|
Sign up to set email alerts
|

The influence of kinesio taping on trunk and lower extremity motions during different landing tasks: implications for anterior cruciate ligament injury

Abstract: Purpose The purpose of the study was to investigate the influence of a 72-h KT application on trunk and lower extremity kinematics during different landing tasks. Methods Twenty-nine competitive male athletes participated in this study. The sum of knee valgus and lateral trunk lean, symmetry index (SI), and peak angles of lateral trunk lean, hip flexion, knee abduction and flexion were assessed for all participants during single-leg drop landing (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This observed neuromuscular adaptation during functional task could potentially reduce the risk for noncontact ACL injury. 34 Furthermore, Sheikhi et al 58 suggest that Kinesio TP application may improve knee abduction and sum of knee valgus and lateral trunk lean during single-leg drop landing, knee flexion during single-leg drop landing and single-leg vertical drop jump in individuals displaying risky single‑leg kinematics. Therefore, Kinesio TP application may marginally improve high‑risk landing kinematics in competitive male athletes, and a systematic review of Ericksen et al 15 concludes that combo FB generates the greatest reductions in peak vertical ground-reaction force during a jump-landing task.…”
mentioning
confidence: 99%
“…This observed neuromuscular adaptation during functional task could potentially reduce the risk for noncontact ACL injury. 34 Furthermore, Sheikhi et al 58 suggest that Kinesio TP application may improve knee abduction and sum of knee valgus and lateral trunk lean during single-leg drop landing, knee flexion during single-leg drop landing and single-leg vertical drop jump in individuals displaying risky single‑leg kinematics. Therefore, Kinesio TP application may marginally improve high‑risk landing kinematics in competitive male athletes, and a systematic review of Ericksen et al 15 concludes that combo FB generates the greatest reductions in peak vertical ground-reaction force during a jump-landing task.…”
mentioning
confidence: 99%
“…Sample size calculations were performed using G*Power (version 3.1.9.2, Dusseldorf, Germany). In accordance with previous evidence 21 31 32 , a medium effect size (f=0.25), an alpha level of 0.05, and a power of 0.80 were considered. The calculation revealed that 22 participants were required in each group.…”
Section: Methodsmentioning
confidence: 92%
“…KT is adopted to improve function, stability, and proprioception [17][18][19] and enhance muscle contraction and force production in painful musculoskeletal conditions [15,19,20]. By improving proprioception and muscle activation, KT may favorably influence injury risk [19,21,22]. Applying KT at a stretch greater than 50 % can help correct the knee valgus position [19,21] and improve jump performance [18,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a forward-flexed trunk position results in greater hip and knee flexion upon landing, reducing landing forces and mitigating ACL injury risk (Blackburn and Padua, 2009). Ipsilateral trunk lean has also been identified as a risk factor for ACL injury, as it causes the ground reaction force vector to shift laterally relative to the knee joint, increasing the load on the medial knee (Hewett et al, 2009;Sheikhi et al, 2021). Specifically, lateral trunk displacement was identified as a risk factor for ACL injury with high sensitivity and specificity in female athletes (Zazulak et al, 2007).…”
Section: Introductionmentioning
confidence: 99%